Combined exposure to CO2 and H2S significantly reduces the performance of the Mediterranean seagrass Posidonia oceanica: Evidence from a volcanic vent - Geraldina Signa; Valentina Sciutteri; Agostino Tomasello; Valentina Costa; Silvia Casabianca; Giovanna Cilluffo; Cristina Andolina; Salvatrice Vizzini (Limnology and Oceanography Letters, 2024)
Although seagrasses are expected to thrive in future acidified oceans by overcoming low CO2 diffusion into plant tissues, the co-occurrence of environmental stressors may affect their growth. Volcanic CO2 vents are often associated with toxic gases and metal-rich fluids representing ideal sites to assess the effects of multiple stressors. We evaluated the response of Posidonia oceanica growing near shallow CO2 vents characterized by H2S spill-out by comparing meadow structure and phenology to an area with no gas emissions. Seagrass descriptors at meadow, shoot and leaf level indicated that P. oceanica experienced stressful conditions at the vent area, in clear contrast to the flourishing features of P. oceanica previously described at CO2 vents with no evidence of toxic inputs. Furthermore, the reduction in both leaf δ34S and growth at the vent area indicates that sulfide intrusion occurs and affects seagrass growth performance, dampening the expected beneficial effects of high CO2 levels.